RELATIONSHIP BETWEEN MATERNAL CHARACTERISTICS AND MENARCHE IN SCHOOLGIRLS AGED 10-12 - Saingu, Mariana; Soelistyoningsih, Dwi; Rahmawati, Wenny (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2024)
Adolescence is a period of change or transition from childhood to adulthood which includes biological, psychological and social changes. The most important event in a child's puberty is the first menstruation or menarche, which is a biological sign of sexual maturity. Examine the correlation between maternal characteristics and menarche readiness for female students aged 10-12 years. This study used correlational analysis with a cross sectional approach. Data collection technique used a questionnaire which was conducted on 89 respondents with menarche readiness students aged 10-12 years at SDK Santo Yusup III Malang. The statistical test used the contingency coefficient test. The results of this study indicated that there was correlation between maternal characteristics and readiness for menarche for students aged 10-12 years at SDK Santo Yusup III Malang, the mother's age had p value = 0.000 (r = 0.372), the last education of the mother was p value of 0.001 (r = 0.480), and mother's menarche age p = 0.002 (r = 0.453), which means there was a correlation between the two variables. The correlation value in this study indicated that the direction of the correlation was positive with a fairly strong correlation strength.Keyword: Characteristics of Mothers, Readiness for Menarche, 10-12 Years Old Student